1988
DOI: 10.1002/bies.950080602
|View full text |Cite
|
Sign up to set email alerts
|

DNA topoisomerases and DNA repair

Abstract: Sum ma ryDNA topoisomerases are enzymes that can modify, and may regulate, the topological state of DNA through concerted breaking and rejoining of the DNA strands. They have been believed to be directly involved in DNA excision repair, and perhaps to be required for the control of repair as well. The vicissitudes of this hypothesis provide a noteworthy example of the dangers of interpreting cellular phenomena without genetic informatior and vice versa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…Earlier reports to the contrary (14) were based on work with less specific topoisomerase inhibitors, novobiocin and nalidixic acid, which have a variety of nontopoisomerase targets; this can produce considerable confusion (20,21). We have shown that the metaphaseanaphase transition is sensitive to specific inhibitors of DNA topoisomerase II, but not of topoisomerase I, both in cells accumulated in mitosis and in unsynchronized PtK2 cells, in a largely reversible manner analogous to the effects of top2 but not top] mutations in yeast (3)(4)(5)(6)(7).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier reports to the contrary (14) were based on work with less specific topoisomerase inhibitors, novobiocin and nalidixic acid, which have a variety of nontopoisomerase targets; this can produce considerable confusion (20,21). We have shown that the metaphaseanaphase transition is sensitive to specific inhibitors of DNA topoisomerase II, but not of topoisomerase I, both in cells accumulated in mitosis and in unsynchronized PtK2 cells, in a largely reversible manner analogous to the effects of top2 but not top] mutations in yeast (3)(4)(5)(6)(7).…”
Section: Discussionmentioning
confidence: 99%
“…DNA topoisomerase I (TOP1) releases torsional stress of DNA through a single-strand breakage/rejoining reaction and plays critical roles in replication, transcription, and DNA damage repair in mammalian cells (1)(2)(3). During the catalytic cycle, the active site tyrosine of TOP1 links covalently to a 3Ј phosphate of DNA at the break site (4).…”
Section: Introductionmentioning
confidence: 99%
“…However, controversy mostly concerns UV-induced excision repair and the use of novobiocin, an agent incorrectly assumed to be a specific inhibitor of the enzyme (Downes & Johnson, 1988). It is premature to rule out involvement of topoisomerase in all repair processes.…”
Section: Resultsmentioning
confidence: 99%